2001
DOI: 10.1152/ajpheart.2001.280.3.h1383
|View full text |Cite
|
Sign up to set email alerts
|

Carotid baroreflex regulation of sympathetic nerve activity during dynamic exercise in humans

Abstract: We sought to determine whether carotid baroreflex (CBR) control of muscle sympathetic nerve activity (MSNA) was altered during dynamic exercise. In five men and three women, 23.8 +/- 0.7 (SE) yr of age, CBR function was evaluated at rest and during 20 min of arm cycling at 50% peak O(2) uptake using 5-s periods of neck pressure and neck suction. From rest to steady-state arm cycling, mean arterial pressure (MAP) was significantly increased from 90.0 +/- 2.7 to 118.7 +/- 3.6 mmHg and MSNA burst frequency (micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
101
1
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(120 citation statements)
references
References 29 publications
15
101
1
3
Order By: Relevance
“…If we then add the average resting value observed in hypoxia to that curve, we can see that the subjects operated in hypoxia on the same baroreflex curve as in normoxia, with a displacement of the operating point along the curve toward the threshold. This is a result of the decrease in P induced by peripheral vasodilation, to which the subjects responded with an increase in f H , supporting the notion that peripheral vascular changes play a significant role in the baroreflex response of resting humans (17,35). If indeed hypoxemia induces vasodilation in peripheral circulation via ␤ 2 -sympathetic stimulation, then we can propose a role for peripheral chemoreflexes in the displacement of the baroreflex operating point in hypoxia.…”
Section: Discussionsupporting
confidence: 72%
“…If we then add the average resting value observed in hypoxia to that curve, we can see that the subjects operated in hypoxia on the same baroreflex curve as in normoxia, with a displacement of the operating point along the curve toward the threshold. This is a result of the decrease in P induced by peripheral vasodilation, to which the subjects responded with an increase in f H , supporting the notion that peripheral vascular changes play a significant role in the baroreflex response of resting humans (17,35). If indeed hypoxemia induces vasodilation in peripheral circulation via ␤ 2 -sympathetic stimulation, then we can propose a role for peripheral chemoreflexes in the displacement of the baroreflex operating point in hypoxia.…”
Section: Discussionsupporting
confidence: 72%
“…Although a linear relationship between spontaneous fluctuations in MSNA and DAP has been demonstrated in previous studies (10,11,33), spontaneous blood pressure fluctuations are not particularly large and so the baroreflex stimulus response range that can be examined by this method is limited (within 20 mmHg). Although this is a narrower range than those obtained with other methods, such as the neck chamber technique (3,8,22,37) or invasive pharmacological manipulation (6, 9), a 20-mmHg change in blood pressure is within the physiological range and should be a good reflection of the arterial baroreflex control of MSNA under physiological conditions. Furthermore, to investigate the reflex effect elicited when two or more inputs are summed (e.g., baroreceptor and muscle metaboreceptor inputs in this study) it is important to use inputs that are small enough not to cause saturation of the output because of any inherent limitation in the effector responses of the system (25).…”
Section: Discussionmentioning
confidence: 81%
“…Total activity is dependent on both burst number and burst strength and represents the level of MSNA more accurately than either of these variables (26,30,32,36). It has been reported that during exercise, the arterial baroreflex operating pressure is reset to a higher pressure than at rest (3,10,22,23,24). Central command, the muscle mechanoreflex, and the muscle metaboreflex have been regarded as possible mechanisms responsible for this resetting (9,10,16,17,(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Full carotid-cardiac baroreflex function curves were derived at rest and during moderate-intensity cycling, as previously described (14,30,36). Briefly, following instrumentation for HR and blood pressure measurements, subjects were fitted with a malleable lead neck collar that encircled the anterior 2/3 of the neck for the application of NP and NS.…”
Section: Methodsmentioning
confidence: 99%